The influence of profitability ratio, market ratio, and solvency ratio on the share prices of companies listed on LQ 45 Index - Abhimada Gatuth Satryo; Nur Aini Rokhmania; Pepie Diptyana (Universitas Hayam Wuruk Perbanas, 2016)
This research aims to analyze the influence of profitability ratio, market ratio, and solvency ratio on the share price of companies listed on LQ 45 Index. The independent variables used in this research is Return on Assets (ROA), Return on Equity (ROE), Earning per Share (EPS), Price to Book Value (PBV), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR), while the dependent variable used is share price. The samples of this study are companies listed on LQ 45 Index in Indonesia Stock Ex-change from 2010 to 2014. The samples are selected by using purposive sampling method and obtained 15 companies that fulfill the criteria specified. Data are processed using Multiple Regression Analysis and statistical test. The results of this study show that Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR) have no effect on share price, while Earning per Share (EPS) and Price to Book Value (PBV) have an effect on share price.